Thermal Energy Systems Design and Analysis, Second Edition. - Penoncello, Steven G. (Milton : Chapman and Hall/CRC, 2018)
Thermal Energy Systems: Design and Analysis, Second Edition presents basic concepts for simulation and optimization, and introduces simulation and optimization techniques for system modeling. This text addresses engineering economy, optimization, hydraulic systems, energy systems, and system simulation. Computer modeling is presented, and a companion website provides specific coverage of EES and Excel in thermal-fluid design. Assuming prior coursework in basic thermodynamics and fluid mechanics, this fully updated and improved text will guide students in Mechanical and Chemical Engineering as they apply their knowledge to systems analysis and design, and to capstone design project work.
2.9.3 Sum of the Years' Digits (SYD)Reference; Problems; Time Value of Money; Economic Decision Making; Depreciation and Taxes; Chapter 3: Analysis of Thermal Energy Systems; 3.1 Introduction; 3.2 Nomenclature; 3.3 Analysis Procedure; 3.4 Conserved and Balanced Quantities; 3.4.1 The Generalized Balance Law; 3.5 Conservation of Mass; 3.6 Conservation of Energy; 3.7 The Entropy Balance (The Second Law of Thermodynamics); 3.7.1 The Reversible and Adiabatic Process; 3.7.2 Isentropic Efficiencies of Flow Devices; 3.7.2.1 Turbines; 3.7.2.2 Compressors, Pumps, and Fans; 3.7.2.3 Nozzles
Description based upon print version of record.
3.7.2.4 Diffusers
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Mechanics / Dynamics / Thermodynamics; TECHNOLOGY & ENGINEERING / Mechanical; Heat engineering; Heat -- Transmission; Thermodynamics -- Data processing